Knowledge on the Environmental Factors Affecting Health of Traffic Police in Kathmandu Valley - Singh, Matrika; Shrestha, Ratika; Yadav, Ajay Kumar; Devkota, Nishchal; Pariyar, Kanchan; Gajurel, Sharad Hari (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Traffic police are the officers who play a vital role in maintaining laws and regulations on the road 24 hours a day. They are exposed to dust, fumes, noise, UV rays, germs and other factors which may have serious potential to cause health problems, which is preventable but may be unaware of it. Hence, this study aims to assess the knowledge of the environmental factors affecting health among traffic police. Methods: A cross-sectional study was conducted among the traffic police of Kathmandu Metropolitan city from December 2021 to May 2022. The selfadministrated questionnaire was provided in different traffic police stations with permission of Metropolitan Traffic Police, Kathmandu. The questionnaire was structured with each separated section of environmental factors. Epidata was used for data entry and analyzed through IBM SPSS. Chi square test was used to measure the significant association of dependent and independent variables. Results: A survey of 352 respondents found that the majority had fair knowledge on environmental factors such as air pollution, microbes, food and water borne diseases and 78.7% had fair knowledge about noise pollution. Dust from vehicular movement was reported as the main source of air pollution, while eye problems 46.6%and allergies 50.2% were the main health and skin problems respectively. Conclusions: It is worrying that only a few traffic police officers have a good understanding of the environmental factors that can harm health. This poses significant public health issues. To address this problem, the study recommends raising awareness among authorities and providing education to traffic police officers and can facilitate change at the grassroots level.